2007
DOI: 10.1177/0891241606293608
|View full text |Cite
|
Sign up to set email alerts
|

Allies Within and Without

Abstract: Most research on youth subordination and age inequality focuses on macrolevel institutions, ideologies, and discourses. While important, this macrolevel focus mystifies the ways in which young people themselves conceptualize and negotiate ageism. This article examines how adolescents collectively experience, politicize, and respond to ageism as they become active in educational justice and antiwar movements. Based on comparative ethnographic research with youth movement organizations in Portland, Oregon and Oa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…Westheimer and Kahne (2004) found that critically conscious urban youth expressed a commitment to a distinct form of citizenship, such that adolescents exhibiting greater levels of critical reflection (i.e., were more aware of perceived social inequalities) are more committed to activism than to conventional political action. Ethnographies also suggest that adolescent activists with greater perceptions of societal inequities are more committed to social action participation than conventional political participation (Gordon, 2007;Taft, 2006). Finally, greater levels of CC-although in this case reflecting an undifferentiated conception of critical reflection and action-were not predictive of marginalized youth's conventional political participation (Diemer, 2012).…”
Section: Intersections Of CC and Political Actionmentioning
confidence: 85%
See 3 more Smart Citations
“…Westheimer and Kahne (2004) found that critically conscious urban youth expressed a commitment to a distinct form of citizenship, such that adolescents exhibiting greater levels of critical reflection (i.e., were more aware of perceived social inequalities) are more committed to activism than to conventional political action. Ethnographies also suggest that adolescent activists with greater perceptions of societal inequities are more committed to social action participation than conventional political participation (Gordon, 2007;Taft, 2006). Finally, greater levels of CC-although in this case reflecting an undifferentiated conception of critical reflection and action-were not predictive of marginalized youth's conventional political participation (Diemer, 2012).…”
Section: Intersections Of CC and Political Actionmentioning
confidence: 85%
“…Critical action refers to participation in individual or collective action to produce social change (Godfrey & Grayman, 2014). Protest, or collective action taken to draw attention to an issue or to protest perceived injustice, is an archetypal form of critical action (Gordon, 2007;Taft, 2006;Watts & Flanagan, 2007) that is examined in this research. (For clarity, this construct is referred to as critical action: protest from this point forward.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Undergraduates, who are of voting age, have more opportunities to become engaged in the political process. The majority of Mr. Monroe's students were at least 2 years from being able to vote, and although research suggests that Downloaded by [University of Colorado -Health Science Library] at 03:41 31 March 2015 adolescents can become involved in the political process (e.g., Diemer & Li, 2011;Gordon, 2007), the opportunities are fewer, and access to the political arena is often more difficult for K-12 students than for adults. Future research is needed to determine whether a greater disciplinary focus in high school civics classes leads to greater political engagement, both as adolescents and as young adults.…”
Section: Discussionmentioning
confidence: 98%